The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/bi052206o
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Anesthetic-Induced Conformational Transitions in a Four-α-Helix Bundle Protein

Abstract: Inhaled anesthetics are thought to alter the conformational states of Cys-loop ligand-gated ion channels (LGICs) by binding within discrete cavities that are lined by portions of four α-helical transmembrane domains. Because Cys-loop LGICs are complex molecules that are notoriously difficult to express and purify, scaled-down models have been used to better understand the basic molecular mechanisms of anesthetic action. In this study, stopped-flow fluorescence spectroscopy was used to define the kinetics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…It has been shown that bound volatile general anesthetics alter both local protein dynamics and global protein stability [65][66][67][68]. Both Ab40 and Ab42 peptides have two a-helices (a-helix-I (residues 15-23), a-helix-II (residues 32-36)) connected by a more flexible kink region.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that bound volatile general anesthetics alter both local protein dynamics and global protein stability [65][66][67][68]. Both Ab40 and Ab42 peptides have two a-helices (a-helix-I (residues 15-23), a-helix-II (residues 32-36)) connected by a more flexible kink region.…”
Section: Discussionmentioning
confidence: 99%
“…Upon exposure to isoflurane, however, both Hsp22 and Hsp27 are upregulated, indicating endoplasmic reticulum involvement in handling the additional proteostatic stress. Wild-type flies experience mild proteostatic stress from both anesthetics, modestly upregulating Hsp27 , consistent with the known potential of volatile anesthetics to interact with hydrophobic compartments of native proteins, thereby modulating protein dynamics and stability and causing conformational changes 40–43 that are aggravated in abnormal proteins. 44 Differential upregulation of Hsp68 , a member of the large Hsp70 family, by isoflurane in ND23 60114 mutants is consistent with the notion that isoflurane’s interaction with the mutant ND23 protein results in more misfolding than sevoflurane’s.…”
Section: Discussionsupporting
confidence: 64%
“…The intercalation and penetration of anesthetics such as short chain alcohols into the cell membrane is believed to affect key ion channels and/or neurotransmitter receptors either directly and/or indirectly by altering physical properties of the membrane. Although physiological levels of ethanol have relatively minor effects on lipid orientational order or dynamics, a transient interaction between ethanol and the glycerol lipid headgroup has been observed by NMR where the bound state lifetime is on the order of a few nanoseconds. , It is therefore tempting to hypothesize that passive diffusion of oxygen through the glycerol headgroup region of the bilayer serves as the rate-limiting step in overall trans-bilayer oxygen transport, and the addition of small amounts of permeabilizers such as DMSO or pentanol might alter lipid packing in this region and thus oxygen transport. This might in turn give rise to a multitude of downstream events associated with oxygen homeostasis.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%